Comparison of posture and musculoskeletal disorders of dentists with high and low work experience - Narges Hosseini; Sajad Roshani (Tehran University of Medical Sciences, 2023)
Background and Aims: Dentists are at risk of musculoskeletal disorders due to their job characteristics. The purpose of this study was to compare the posture and musculoskeletal disorders of dentists with high and low work experience. Materials and Methods: This analytical cross-sectional study research was conducted on 76 dentists in Urmia city. Based on work experience, the samples were divided into two groups: less experienced (less than 15 years) and experienced (15 years and more). The variables of forward head, kyphosis, round shoulder, and musculoskeletal disorders were compared in two groups. Forward head and round shoulder variables were evaluated by photography, kyphosis variable by flexible ruler, and musculoskeletal disorders were evaluated by Nordic questionnaire. Data analysis was done using descriptive statistics and analytical statistics (Kolmogorov-Smirnov test, Leven test, independent t-test and Yeoman-Whitney test). Results: The independent t-test results showed that the angle of forward head, round shoulder, and kyphosis was higher in the high work-experience group than that of the low work-experience group (P=0.001). In comparing the prevalence of neck disorders, the results were significant such that the experienced group had more neck disorders (P=0.002). However, in examining the difference in the amount of disorders in other parts of the body, the difference between the two groups was not statistically significant (P>0.05). Conclusion: Experienced dentists had a higher degree of forward head, round shoulder and kyphosis positions. Although, there are musculoskeletal disorders in both groups of dentists with low and high level of experience, neck disorders were more common in high-experienced dentists than that of low-experienced ones.